POTRET WANITA BERITA KRIMINAL PEMERKOSAAN DI MEDIA ONLINE SINDONEWS.COM - Rina Ari Rohmah (JURNAL PENDIDIKAN ROKANIA, 2017)
This study aims to describe the shape and meaning of female portraits in crime rape news contained in online media Sindonews.com. This research uses a criticalqualitative approach by focusing on Sara Mills text analysis. Research data in the form of vocabulary, phrase, or sentence that shows the form and meaning ofthe portrait of women in the news. The results showed that the form and meaning of the text in the rape crime news can be seen from the position of the subject-object and the position of the author-reader. From the subjectobject side, the whole news text describes the perpetrator as the subject and the victim as the object. The meaning of the portrait of women in the news of rape crime in online media sindonews.com that women tend to be marginalized. Women described as people who are blamed or people who have a bad image. Instead, men are presented and displayed in a good image because he or she tells the story.